Palenie papierosów w ciąży = Cigarette smoking in pregnancy - Agnieszka Konstancja Pawłowska-Muc; Celina Łepecka-Klusek; Anna Bogusława Pilewska-Kozak; Grażyna Stadnicka; Klaudia Pałucka (Kazimierz Wielki University, 2016)
Pawłowska-Muc Agnieszka Konstancja, Łepecka-Klusek Celina, Pilewska-Kozak Anna Bogusława, Stadnicka Grażyna, Pałucka Klaudia. Palenie papierosów w ciąży = Cigarette smoking in pregnancy. Journal of Education, Health and Sport. 2016;6(1):73-84. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44638 http://ojs.ukw.edu.pl/index.php/johs/article/view/44638 http://pbn.nauka.gov.pl/works/692522 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.12.2015. Revised 25.12.2015. Accepted: 09.01.2016.   Palenie papierosów w ciąży Cigarette smoking in pregnancy   Pawłowska-Muc Agnieszka Konstancja1, Łepecka-Klusek Celina2, Pilewska‑Kozak Anna Bogusława2, Stadnicka Grażyna3, Pałucka Klaudia4   [1] Ośrodek Kształcenia Podyplomowego Pielęgniarek i Położnych Radomski Szpital Specjalistyczny im. dr Tytusa Chałubińskiego w Radomiu, ul. Lekarska 4 2 Katedra i Klinika Ginekologii i Endokrynologii Ginekologicznej Uniwersytet Medyczny w Lublinie, Al. Racławickie 23 3 Samodzielna Pracownia Umiejętności Położniczych Uniwersytet Medyczny w Lublinie, ul. Staszica 4/6 4 Doktorantka w Katedrze i Klinice Ginekologii i Endokrynologii Ginekologicznej Uniwersytet Medyczny w Lublinie, Al. Racławickie 23 1 Postgraduate Training Centre for Nurses and Midwives, Dr Tytus Chałubiński Specialist Hospital in Radom, ul. Lekarska 4 2 Department and Clinic of Gynaecology and Gynaecological Endocrinology, School of Health Studies, Medical University of Lublin, Al. Racławickie 23 3 Independent Obstetric Skills Workshop, Medical University of Lublin, ul. Staszica 4/6 4 Doctoral Candidate at the Department and Clinic of Gynaecology and Gynaecological Endocrinology, School of Health Studies, Medical University of Lublin, Al. Racławickie 23   Adres do korespondencji: mgr piel. Agnieszka Konstancja Pawłowska-Muc Ośrodek Kształcenia Podyplomowego Pielęgniarek i Położnych Radomski Szpital Specjalistyczny im. dr Tytusa Chałubińskiego w Radomiu, ul. Lekarska 4 tel. 48  3615616; fax: 48 3615437 e-mail: agmich@vp.pl   Streszczenie Wprowadzenie. Palenie papierosów jest dużym problemem zdrowotnym i społeczno - ekonomicznym. Stanowi zagrożenie dla rozrodu, przebiegu ciąży i zdrowia dziecka. Cel pracy. Ukazanie problemu palenia papierosów przez kobiety ciężarne na podstawie przeglądu piśmiennictwa.             Skrócony opis stanu wiedzy. W opracowaniu przedstawiono epidemiologię i skalę problemu oraz konsekwencje palenia w okresie ciąży, z uwzględnieniem podziału na przebieg ciąży i zdrowie dziecka. Omówiono też świadomość kobiet odnośnie negatywnych skutków takich zachowań. Podsumowanie. Z przeglądu piśmiennictwa wynika, że palenie papierosów przez kobiety ciężarne nie należy do rzadkości. Skala problemu nie jest łatwa do oceny, gdyż wiele z nich po prostu nie przyznaje się do tego. Negatywne konsekwencje palenia w ciąży są dość liczne i dotyczą zarówno jej przebiegu, jak i stanu noworodka oraz zdrowia dziecka w późniejszym okresie życia. Istnieje potrzeba kształtowania postaw antynikotynowych, zwłaszcza wśród dziewcząt i kobiet w wieku rozrodczym.   Słowa kluczowe: kobieta ciężarna, palenie papierosów w ciąży.                                                                   Summary Introduction. Smoking cigarettes is a major health and social-economical problem. It poses a threat to reproduction, parturition and the health of the baby. Aim. Illustrating the problem of smoking cigarettes by pregnant women on the basis of the review of the bibliography.             Brief description of the state of the art. This research demonstrates the epidemiology and the scale of the problem as well as the consequences of smoking during pregnancy taking into consideration the division into the parturition and the health of the baby. It also discusses women's awareness of the negative effects of such behaviours. Conclusion. The review of the bibliography indicates that smoking cigarettes by pregnant women is not uncommon. The scale of the problem is not easy to assess due to the fact that many of these women simply do not admit to it. The negative consequences of smoking during pregnancy are quite numerous and pertain to both the parturition and the state of the newborn as well as the health of the child at a later stage in its life. This calls for the need to shape anti-nicotine attitudes, especially in girls and women in the reproductive period.   Key words: pregnant woman, smoking during pregnancy.